2020
DOI: 10.1007/s12028-020-01077-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation use and Hemorrhagic Stroke in SARS-CoV-2 Patients Treated at a New York Healthcare System

Abstract: Background and Purpose: While the thrombotic complications of COVID-19 have been well described, there are limited data on clinically significant bleeding complications including hemorrhagic stroke. The clinical characteristics, underlying stroke mechanism, and outcomes in this particular subset of patients are especially salient as therapeutic anticoagulation becomes increasingly common in the treatment and prevention of thrombotic complications of COVID-19. Methods: We conducted a retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 26 publications
0
90
0
1
Order By: Relevance
“…Up to 89.5% of the patients positive to SARS-CoV-2 with ICH were under empiric anticoagulation. 70 As frequently reported in the literature, anticoagulant-related ICH occurs predominantly in a lobar and/or cortico-subcortical location. 154,155 In line with it, a greater prevalence of hemorrhagic transformation of ischemic strokes was reported in SARS-CoV-2-positive patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Up to 89.5% of the patients positive to SARS-CoV-2 with ICH were under empiric anticoagulation. 70 As frequently reported in the literature, anticoagulant-related ICH occurs predominantly in a lobar and/or cortico-subcortical location. 154,155 In line with it, a greater prevalence of hemorrhagic transformation of ischemic strokes was reported in SARS-CoV-2-positive patients.…”
Section: Discussionmentioning
confidence: 87%
“…69 According to Kvernland et al, 89.5% of the patients with hemorrhagic stroke were on anticoagulation. 70 In this context, an underlying COVID-19-induced endotheliopathy is discussed, complicating anticoagulation decision, as clinicians have to balance risk of thrombosis with risk of ICH.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…A higher mortality rate was observed in COVID-19 patients compared to both contemporary and historical negative controls with ICH. 58 In another cohort, all COVID-19 patients with hemorrhagic lesions on brain MRI suffered from acute respiratory distress syndrome and were hospitalized in intensive care units. 88 A total of 20% patients with hemorrhagic lesions died during hospitalization, compared with 6% of COVID-19 patients with other non-hemorrhagic lesions.…”
Section: Resultsmentioning
confidence: 99%
“…31 Another study from the United States found that 19 (0.5%) patients developed hemorrhagic stroke, in which therapeutic anticoagulation was prescribed in 89.5% of these patients. 55 Full anticoagulation is now being provided for hospitalized COVID-19 patients in many centers. However, rates of bleeding in such patients appear to be high.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%